1997
DOI: 10.1590/s0100-879x1997000200016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cyclopiazonic acid on intracellular Ca2+ in aortic smooth muscle cells from DOCA-hypertensive rats

Abstract: We tested the hypothesis that cyclopiazonic acid (CPA), an inhibitor of the sarcoplasmic reticulum (SR) Ca 2+ -ATPase, increases intracellular Ca 2+ concentration ([Ca 2+ ] i ) in aortic myocytes and that the increase in [Ca 2+ ] i is higher in aortic cells from deoxycorticosterone acetate (DOCA)-hypertensive rats. Male Sprague-Dawley rats, 250-300 g, underwent uninephrectomy, received a silastic implant containing DOCA (200 mg/kg) and had free access to water supplemented with 1.0% NaCl and 0.2% KCl. Control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Smooth muscle cells and isolated vascular tissue from SHR and DOCA-salt rats have been shown to have greater basal and agonist-induced intracellular calcium concentrations, as well as heightened sensitivity to the calcium channel agonist Bay K 8644, possibly mediated by an increased activity of voltage gated Ca ++ channels [27][28][29]. An increased response to depolarization stimuli (potassium chloride) in isolated tissue also supports the role of altered Ca ++ channels in hypertension.…”
Section: Increased Vasoconstrictor Sensitivity In Hypertensionmentioning
confidence: 84%
“…Smooth muscle cells and isolated vascular tissue from SHR and DOCA-salt rats have been shown to have greater basal and agonist-induced intracellular calcium concentrations, as well as heightened sensitivity to the calcium channel agonist Bay K 8644, possibly mediated by an increased activity of voltage gated Ca ++ channels [27][28][29]. An increased response to depolarization stimuli (potassium chloride) in isolated tissue also supports the role of altered Ca ++ channels in hypertension.…”
Section: Increased Vasoconstrictor Sensitivity In Hypertensionmentioning
confidence: 84%
“…Vascular smooth muscle cells (VSMC) were isolated from rat thoracic aortas according to the method described by Tostes et al (1997). Briefly, the thoracic aorta was rapidly removed, placed in 0.1 mM Ca 2+ Hank's solution at 22 -C, cleaned of fat and connective tissue.…”
Section: Measurement Of Cytosolic Ca 2+ Concentration In Aortic Smootmentioning
confidence: 99%
“…Under similar conditions, VSMCs isolated from the thoracic aorta of DOCA-salt rats exhibit an increase in [Ca 2+ ] i while no changes are observed in normotensive cells. Contractions and increases in [Ca 2+ ] i do not occur in the presence of the Ca 2+ channel antagonist, nifedipine (21). Other investigators have demonstrated that high concentrations of Ca 2+ induce contractions in aortic segments from spontaneously hypertensive rats (SHR) but do not alter tone in those from normotensive rats (3).…”
Section: Abnormalities Of Vascular Function Vs Ca 2+ Handlingmentioning
confidence: 99%